Skrining Kualitatif Fitokimia Senyawa Metabolit Sekunder pada Daun Jeruk Purut (Citrus hystrix) - Masyitah Masyitah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Citrus hystrix DC., commonly known as kaffir lime, is a citrus plant widely distributed in Southeast Asia including Indonesia, Thailand, India, and China. Its leaves are traditionally used as food flavoring and herbal medicine due to their distinctive aroma and therapeutic potential. This study was conducted to identify the presence of secondary metabolite compounds in kaffir lime leaves through qualitative phytochemical screening. Fresh leaves were extracted and tested using standard phytochemical methods with specific reagents to detect alkaloids, flavonoids, phenolics, tannins, saponins, steroids, and terpenoids. The screening process was carried out through colorimetric reactions that indicate the presence of specific metabolite groups. The results showed that kaffir lime leaves positively contain several classes of secondary metabolites, including alkaloids (brownish-black precipitate with Bouchardat reagent), flavonoids (red color with Mg and concentrated HCl), saponins (stable foam formation after shaking with HCl), steroids (green color with acetic anhydride), terpenoids (reddish-purple color with concentrated H2SO4), and tannins (greenish-black color with FeCl3). The findings confirm that kaffir lime leaves are rich in bioactive compounds that may contribute to pharmacological activities such as antimicrobial, antioxidant, anti-inflammatory, and therapeutic properties. These results support the traditional use of kaffir lime leaves as natural medicine and highlight their potential as a source of natural bioactive compounds for further pharmaceutical and nutraceutical development. This study provides preliminary scientific evidence and encourages more detailed quantitative and isolation studies on the active components of Citrus hystrix.